Analisa Kekuatan Struktur Barge Pada Proses Load Out Offshore Module (Top Side) dengan SPMT - Habibi Palippui; Sahwan Ramadhan (Departemen Teknik Kelautan Universitas Hasanuddin, 2020)
One of the critical processes when fabricating offshore is the process of transferring the offshore module (Top Side) from the top of the jetty to the transportation barge or often called the process Load Out. One of the analyzes needed to ensurethe processing load out runs smoothly and safely is the analysis of the strength of the barge structure when the load out process occurs, which is checking the strength of the barge structure whether it is able to withstand the load topside when there is load transfer from the top of the jetty to transportation barge or from the edge of the barge to the final location. To get accurate results, the help of computer programs is used or often called the finite element method (Finite Element Analysis). The software used in this analysis is Staad Pro V8i with a three-module simulation experiment. From theanalysis it was concluded that the three module simulation simulations have a maximum value of von mises stress is 74.119 N / mm2, normal stress is 57.765 N / mm2, and shear stress is 0.02279 N / mm2, where all stress values are below the maximum limit required by the American Institute of Steel Construction ( AISC) so that the barge structure does not need to be given additional reinforcement both internally and externally because it is still safe and able to withstand the topside when loading. Analysis with SPMT has the potential to be a benchmark in analyzing the strength of the barge structure in the process of loading out the offshore module (top side).